Using the given table of transforms,
![L\left\{ y'' - y' - 2y \right\} = L\left\{ 1-x \right\}](https://img.qammunity.org/2023/formulas/mathematics/college/x0xkim1mg2t7e018urkqcckdplb7q2czso.png)
![(s^2 Y(s) - sy(0) - y'(0)) - (s Y(s) - y(0)) - 2 Y(s) = \frac1s - \frac1{s^2}](https://img.qammunity.org/2023/formulas/mathematics/college/6trrsvz45smwyjmuhkjgq1imvtacqbbd1n.png)
(where Y(s) is the Laplace transform of y(x))
Solve for Y(s) :
![(s^2 - s - 2) Y(s) - s = \frac1s - \frac1{s^2}](https://img.qammunity.org/2023/formulas/mathematics/college/2tgztoj9b0i3dy3eo9s08g72x2vj72jc68.png)
![(s^2 - s - 2) Y(s) - s = (s-1)/(s^2)](https://img.qammunity.org/2023/formulas/mathematics/college/b33w1tlt77iyx35kd6f3ch9per16bqkqvj.png)
![(s^2 - s - 2) Y(s) = (s-1)/(s^2) + s](https://img.qammunity.org/2023/formulas/mathematics/college/c4fyyx86jd7x7rd4eliu7zqvpug9tow02q.png)
![(s^2 - s - 2) Y(s) = (s^3 + s - 1)/(s^2)](https://img.qammunity.org/2023/formulas/mathematics/college/p7axnz7gfyzjyr3fxz2f2l0zlu0rgb4kt3.png)
![Y(s) = (s^3 + s - 1)/(s^2 (s^2 - s - 2))](https://img.qammunity.org/2023/formulas/mathematics/college/v4bl97spn6k8x6qpkj9gs4w678t64ho0fo.png)
![Y(s) = (s^3 + s - 1)/(s^2 (s + 1) (s - 2))](https://img.qammunity.org/2023/formulas/mathematics/college/qpm7xa69ws7h7yws2umgzbpmmjbmaiyvbv.png)
Decompose the right side into partial fractions:
![Y(s) = \frac as + \frac b{s^2} + \frac c{s+1} + \frac d{s-2}](https://img.qammunity.org/2023/formulas/mathematics/college/gs1c0xw7nehtjmw14112w5oknbmnys4f15.png)
Solve for the coefficients.
![\implies s^3 + s - 1 = as(s+1)(s-2) + b(s+1)(s-2) + cs^2(s-2) + ds^2(s+1)](https://img.qammunity.org/2023/formulas/mathematics/college/p9sster5wcdd4xugpoo94qm3pj9lylnw0q.png)
![\implies s^3 + s - 1 = -2 b + (-2 a - b) s + (-a + b - 2 c + d) s^2 + (a + c + d) s^3](https://img.qammunity.org/2023/formulas/mathematics/college/bt5snzoqpdkii504vz0pelj62ajeumbbej.png)
![\implies \begin{cases}-2b = -1 \\ -2a-b = 1 \\ -a+b-2c+d = 0 \\ a+c+d = 1 \end{cases} \implies a=-\frac34, b=\frac12, c=1, d=\frac34](https://img.qammunity.org/2023/formulas/mathematics/college/k32k407w5fy3eq9ttnsu6k1v8pbf4zfv97.png)
Then
![Y(s) = -\frac34 * \frac1s + \frac12 * \frac1{s^2} + \frac1{s+1} + \frac34 *\frac1{s-2}](https://img.qammunity.org/2023/formulas/mathematics/college/cog0x79864cpbnox0ylw6b68t8ebq7dhja.png)
Take the inverse transform and solve for y(x) :
![F(s) = \frac1s \implies f(x) = 1](https://img.qammunity.org/2023/formulas/mathematics/college/25cf079oulms1bw0ycwjadbjgggajmbl9e.png)
![F(s) = \frac1{s^2} \implies f(x) = x](https://img.qammunity.org/2023/formulas/mathematics/college/cr9jgz7lk50vfbb8zeclvp27qjkkyzal60.png)
Using the frequency-shifting property,
![F(s) = \frac1{s+1} \implies f(x) = e^(-x)](https://img.qammunity.org/2023/formulas/mathematics/college/za8w4ifu5z8uqtnpq1qnfrhmjof3nedy4a.png)
![F(s) = \frac1{s-2} \implies f(x) = e^(2x)](https://img.qammunity.org/2023/formulas/mathematics/college/11xodqkeatdoh9om05f6mqtlbmmj2wy6ml.png)
So, the particular solution to the ODE is
![\boxed{y(x) = -\frac34 + \frac x2 + e^(-x) + \frac{3e^(2x)}4}](https://img.qammunity.org/2023/formulas/mathematics/college/h2fxu7bdc9ep8axhdsvkz9tnmulzmetm36.png)